2021
DOI: 10.3390/su14010374
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Reduction of CO2 to Methanol by Cu2O/TiO2 Heterojunctions

Abstract: The conversion of CO2 to low-carbon fuels using solar energy is considered an economically attractive and environmentally friendly route. The development of novel catalysts and the use of solar energy via photocatalysis are key to achieving the goal of chemically reducing CO2 under mild conditions. TiO2 is not very effective for the photocatalytic reduction of CO2 to low-carbon chemicals such as methanol (CH3OH). Thus, in this work, novel Cu2O/TiO2 heterojunctions that can effectively separate photogenerated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…The characteristic absorption band at 560–700 nm observed for TiCu-2 to TiCu-4 is associated with the d–d transition of Cu 2+ . The peak broadening and shift of absorption edge to the visible region observed in Cu x O/TiO 2 are due to the intrinsic adsorption of copper oxides with a narrow band gap . The optical band gap ( E g ) energies of TiO 2 and Cu x O/TiO 2 samples were calculated using the Kubelka–Munk method, and the results are shown in Figure b and Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic absorption band at 560–700 nm observed for TiCu-2 to TiCu-4 is associated with the d–d transition of Cu 2+ . The peak broadening and shift of absorption edge to the visible region observed in Cu x O/TiO 2 are due to the intrinsic adsorption of copper oxides with a narrow band gap . The optical band gap ( E g ) energies of TiO 2 and Cu x O/TiO 2 samples were calculated using the Kubelka–Munk method, and the results are shown in Figure b and Table .…”
Section: Resultsmentioning
confidence: 99%
“…34 The peak broadening and shift of absorption edge to the visible region observed in Cu x O/TiO 2 are due to the intrinsic adsorption of copper oxides with a narrow band gap. 35 The optical band gap (E g ) energies of TiO 2 and Cu x O/TiO 2 samples were calculated using the Kubelka− Munk method, and the results are shown in Figure 3b and Table 1. The enlarged version of the Tauc plot is also shown in the inset of Figure 3b.…”
Section: Optical Properties Of Tio 2 and Cumentioning
confidence: 99%
“…53 Since then, extensive research has been conducted on the implementation of TiO 2 in photocatalytic CO 2 reduction under visible and UV irradiation, starting with the investigation of pristine TiO 2 and its subsequent combination with diverse materials to assess the impact of metal doping. [54][55][56] A case study was conducted on a porphyrin-based MOF, where we observed a notable enhancement in the photocatalytic conversion of CO 2 to CH 3 OH when Cu 2+ was introduced. The presence of Cu 2+ resulted in a remarkable sevenfold increase in the rate of CH 3 OH production compared to the sample without Cu 2+ .…”
Section: Catalysis Science and Technology Reviewmentioning
confidence: 90%
“…53 Since then, extensive research has been conducted on the implementation of TiO 2 in photocatalytic CO 2 reduction under visible and UV irradiation, starting with the investigation of pristine TiO 2 and its subsequent combination with diverse materials to assess the impact of metal doping. 54–56…”
Section: Green Fuelsmentioning
confidence: 99%
“…Cu 2 O can be used as a co-catalyst or main catalyst to hybridize with other semiconductors, obtaining composite materials with multiple superior properties simultaneously. It is a "kill three birds with one stone" strategy to build heterojunction between p-type Cu 2 O and n-type semiconductor materials, such as TiO 2 , [139,140,[168][169][170] WO 3 , [142] Fe 2 O 3 , [171][172][173] Bi 2 Se 3 , [174] MnCo 2 O 4 [175] or WO 3 . [176,177] First, the carrier separation ability of Cu 2 O-based catalysts can be significantly improved.…”
Section: Hybrid Engineeringmentioning
confidence: 99%